INTRODUCING THE CAMEL - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
INTRODUCING THE CAMEL by Peter Gill 149pp spiral bound price US$5.00 plus postage Growing vegetables in Fiji by Kirk Dahlgren price US$5.00 plus postage Both available from ECHO, 17430 Durrance Road, North Fort Myers FL 33917, USA